Influence of symbiotic bacteria on the susceptibility of Plagiodera versicolora to Beauveria bassiana infection - Liu, Mei; Ding, Jinli; Lu, Min (Frontiers in Microbiology, 2023)
The symbiotic bacterial microbiota of insects has been shown to play essential roles in processes related to physiology, metabolism, and innate immunity. In this study, the symbiotic microbiome of Plagiodera versicolora at different developmental stages was analyzed using 16S rRNA highthroughput sequencing. The result showed that symbiotic bacteria community in P. versicolora was primarily made up of Actinobacteriota, Proteobacteria, Firmicutes, Bacteroidota and Dependentiae. The bacterial composition among different age individuals were highly diverse, while 65 core genera were distributed in all samples which recommend core bacterial microbiome. The 8 species core bacteria were isolated from all samples, and all of them were classified as Pseudomonas sp. Among them, five species have been proven to promote the vegetable growth of Beauveria bassiana. Moreover, the virulence of B. bassiana against nonaxenic larvae exceeded B. bassiana against axenic larvae, and the introduction of the Pseudomonas sp. to axenic larvae augmented the virulence of fungi. Taken together, our study demonstrates that the symbiotic bacterial of P. versicolora are highly dissimilarity, and Pseudomonas sp. core bacteria can promote host infection by entomopathogenic fungus. This result emphasizes the potential for harnessing these findings in the development of effective pest management strategies.